Constructing an Al2O3/(NH4)2V4O9 heterostructure as a cathode material for high performance aqueous rechargeable zinc ion batteries. Issue 47 (14th November 2022) - Zhang, Lu; Hou, Lihua; Sheng, Rui; Li, Di; Gu, Yuanxiang; Wang, Lei
Abstract : The presence of an appropriate amount of Al2 O3 makes NH4 V4 O10 change into a mixture of NH4 V4 O9 and Zn3 (OH)2 V2 O7 ·2H2 O to act as an active cathode for high capacity aqueous zinc ion batteries during the cycling process. Abstract : An Al2 O3 /(NH4 )2 V4 O9 heterostructure is fabricated as a cathode material for aqueous rechargeable zinc ion batteries. This is the first report that Al2 O3 assists (NH4 )2 V4 O9 to improve the electrochemical performance of zinc-ion batteries. The Al2 O3 content in the Al2 O3 /(NH4 )2 V4 O9 heterostructure can be controlled by adjusting the ratio of Al : V, and the Al2 O3 /(NH4 )2 V4 O9 nanoblocks with an Al2 O3 content of 15.98% deliver excellent electrochemical performance with a maximum discharge capacity of 269 mAh g −1 at a current density of 0.5 A g −1 . At a high current density of 5.0 A g −1, the Al2 O3 /(NH4 )2 V4 O9 cathode displays an activated maximum capacity of 200 mA h g −1, and the specific capacity can be maintained at 173 mAh g −1 with a maximum capacity retention of 86.5% after 3000 cycles. The excellent electrochemical performance mainly come from the internal electronic field at the heterointerfaces in the Al2 O3 /(NH4 )2 V4 O9 heterostructure.